Going clear : Scientology, Hollywood, and the prison of belief - Wright, Lawrence, 1947- (New York : Alfred A. Knopf, 2013)
"Based on more than two hundred personal interviews with both current and former Scientologists--both famous and less well known--and years of archival research, Lawrence Wright uses his extraordinary investigative skills to uncover for us the inner workings of the Church of Scientology: its origins in the imagination of science-fiction writer L. Ron Hubbard; its struggles to find acceptance as a legitimate (and legally acknowledged) religion; its vast, secret campaign to infiltrate the U.S. government; its vindictive treatment of critics; its phenomenal wealth; and its dramatic efforts to grow and prevail after the death of Hubbard"--From publisher description.
Pt. I. Scientology. The convert -- Source -- Going overboard -- pt. II. Hollywood. The faith factory -- Dropping the body -- In service to the stars -- The future is ours -- Bohemian rhapsody -- TC and COB -- pt. III. The prison of belief. The investigation -- Tommy -- Epilogue.
Includes bibliographical references (p. [373]-418) and index.
Keywords: Scientology; Scientology -- Doctrines; Hubbard, L. Ron -- 1911-1986.; Scientology